2014
DOI: 10.1364/oe.22.000931
|View full text |Cite
|
Sign up to set email alerts
|

Cosine-Gaussian correlated Schell-model pulsed beams

Abstract: A new class of partially coherent pulses of Schell type with cosine-Gaussian temporal degree of coherence is introduced. Such waves are termed the Cosine-Gaussian Schell-model (CGSM) pulses. The analytic expression for the temporal mutual coherence function of the CGSM pulse in dispersive media is derived and used to study the evolution of its intensity distribution and its temporal degree of coherence. Further, the numerical calculations are performed in order to show the dependence of the intensity profile a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…That is, the mean temporal intensity and the spectral density of the pulse train are both Gaussian functions, as are the two-time degree of * matias.koivurova@uef.fi temporal coherence and the two-frequency degree of spectral coherence, which both depend on the appropriate coordinate difference only. Considering some of the more exotic correlation functions, one can readily produce similar effects in time domain as one has in the spatial domain, including acceleration of the intensity peak, pulse self-splitting, and pulse flat topping [44][45][46][47]. Out of these, temporal self-splitting is of potential interest in optical data transmission, since it may open up the possibility to encrypt data in a way that unravels itself upon propagation.…”
Section: Introductionmentioning
confidence: 99%
“…That is, the mean temporal intensity and the spectral density of the pulse train are both Gaussian functions, as are the two-time degree of * matias.koivurova@uef.fi temporal coherence and the two-frequency degree of spectral coherence, which both depend on the appropriate coordinate difference only. Considering some of the more exotic correlation functions, one can readily produce similar effects in time domain as one has in the spatial domain, including acceleration of the intensity peak, pulse self-splitting, and pulse flat topping [44][45][46][47]. Out of these, temporal self-splitting is of potential interest in optical data transmission, since it may open up the possibility to encrypt data in a way that unravels itself upon propagation.…”
Section: Introductionmentioning
confidence: 99%
“…Martínez-Herrero and co-workers derived the necessary and sufficient nonnegative definiteness conditions for the cross-spectral density and the cross-spectral density matrix [47,48]. Based on the this pioneer work, a variety of partially coherent beams with nonconventional correlation functions, such as beams with locally varying spatial coherence [49], scalar and electromagnetic nonuniformly correlated beams [50,51], scalar and electromagnetic nonuniformly correlated partially coherent pulses [52,53], scalar and electromagnetic multi-Gaussian correlated Schell-model beams [54][55][56][57][58], multi-Gaussian correlated Schell-mode vortex beams [59], Laguerre-Gaussian correlated Schell-model beams [60], Bessel-Gaussian correlated Schell-model beams [60], elliptical Laguerre-Gaussian correlated Schell-model beams [61], Laguerre-Gaussian correlated Schell-model vortex beams [62], cosine-Gaussian correlated Schell-model beams [63,64], cosine-Gaussian correlated Schell-model pulsed beams [65] and a special correlated partially coherent vector beam [66], were introduced recently. Propagation properties of those beams have been studied in detail , and it was found that those beams exhibit extraordinary propagation properties, such as far-field flattopped, ring-shaped, four-beamlet array intensity profile formation, self-splitting effect, self-focusing effect, lateral shift of the intensity maximum, and reduction of scintillation in turbulent atmosphere, which are useful in free-space optical communications and optical trapping.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Owing to these advantages and other applications, the generation and propagation of partially coherent beams have attracted much attention. For instance, partially coherent beams with different types of correlation, including Gaussian Schell-model arrays, 4 multi-Gaussian correlated Schell-model beams, 5 and cosine-Gaussian Schell-model beams 6,7 have been produced. Further to this, the propagation of partially coherent beams in atmospheric turbulence, 8,9 oceanic turbulence, [10][11][12] and isotropic random media 13 has also been investigated.…”
Section: Introductionmentioning
confidence: 99%